Membongkar supersemar: Dari CIA hingga kudeta merangkak melawan Bung Karno / Baskara T. Wardaya Sj ; penyunting Islah Yusmian dan JF Tualaka - BASKARA T, WARDAYA; Islah Gusmian; Tualaka, JF (Galang Press, 2009)
356 hlm .: ilus .; 23 cm + CD